Sources and sinks of bottom water oxygen in a seasonally hypoxic fjord - Rakshit, Subhadeep; Dale, Andrew W.; Wallace, Douglas W.; Algar, Christopher Kenneth (Frontiers in Marine Science, 2023)
Deoxygenation of the ocean has been occurring over the last half century, particularly in poorly ventilated coastal waters. In coastal and estuarine environments, both the water column and sediments play key roles in controlling oxygen variability. In this study, we focus on controls of oxygen concentration in Bedford Basin (BB), a 70 m deep, seasonally hypoxic semi-enclosed fjord on the West Atlantic coast in Nova Scotia. The basin is connected to the Scotian Shelf via a narrow 20 m deep sill that restricts the resupply of bottom water. Hypoxia was recorded seasonally in 2018, 2019 and 2021 with minimum oxygen concentration of 5, 6.7 and 2.7 μM, respectively. Using a 1-D benthic-pelagic coupled model we investigate oxygen consumption and resupply processes during these years. The model was constrained with weekly water column measurements of temperature, salinity, chlorophyll-a fluorescence and dissolved oxygen from a monitoring station in the central basin together with seasonal measurements of benthic diffusive oxygen uptake. Our model suggested that 29-81%, and up to 36% of bottom water re-oxygenation occurred during the winter mixing period and through summer/fall intrusions of Scotian Shelf water, respectively. Occasional shelf water intrusions occurred rapidly, on a timescale of a few hours, and delivered equivalent amounts of oxygen as winter mixing and were sufficient to end bottom water hypoxia. Collectively, these mechanisms supplied the majority of the oxygen delivered to the bottom water. Oxygen supply to bottom waters during periods of water column stratification accounted for 19-36% of the annual flux. The mean benthic uptake was 12 ± 8 mmol m-2 d-1 and contributed ~20% of the total oxygen consumption below the sill depth. In 2021, sea surface temperature (SST) was unusually high and likely resulted in 50% less bottom water oxygenation compared to 2018 and 2019 due to increased stratification; SST in BB was found to be increasing at a rate of 0.11 ± 0.02 °C/year. Climate control on water column stratification are discussed and numerical experiments are used to compare the effects of different water column mixing scenarios on bottom water oxygenation.